التعبير الاصطلاحى ومشكلاته في ترجمة - Yunaldi Yunaldi (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2020)
Translation is a subject studied by students at any university in Indonesia. This subject has difficulties and special problems in its teaching, and many students from male and female students do not define it in depth, but they do not feel the most important of this study in the process of teaching and learning the foreign language, especially for non-native speakers. Many of them do not understand that the unity of the end of foreign language teaching at the Islamic University means skill and art of translation. Therefore, the writer writes in this writing translation problems that mean idiomatic expression and its problems in translation with the basic issue. Common mistakes in translating idiomatic expression in Arabic male and female students at the fourth level in the Islamic University of Bading Sadebwan. And this study, Al-Maktabi researched the descriptive and analytical method of translation material at the fourth level, the Arabic Language Department, by providing evidence that the researcher organized and sends the test to them using the Internet. From this study, the writer obtained the following: a) A lack of understanding of the skill of translation in Arabic male and female students, b) Common mistakes in the translation of idiomatic expression facing male and female students) Problems that guide male and female students in the study of translation from a linguistic aspect, including many Arabic vocabulary and rich so that they do not It is easy to give and choose the Arabic Fatat identical to another language. The conclusion of this study is concerned with the lecturer that upgrading the understanding of male and female students' translation in the subject matter of translation, especially the idiomatic expression